2011
DOI: 10.1088/0004-637x/739/2/95
|View full text |Cite
|
Sign up to set email alerts
|

Velocity Structure and Variability of [O Iii] Emission in Black Hole Host Globular Cluster Rz2109

Abstract: We present a multi-facility study of the optical spectrum of the extragalactic globular cluster RZ2109, which hosts a bright black hole X-ray source. The optical spectrum of RZ2109 shows strong and very broad [O III]λλ4959,5007 emission in addition to the stellar absorption lines typical of a globular cluster. We use observations over an extended period of time to constrain the variability of these [O III] emission lines. We find that the equivalent width of the lines is similar in all of the datasets; the cha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(37 citation statements)
references
References 24 publications
3
34
0
Order By: Relevance
“…As discussed in Section 3.4, the nebular emission lines are broad in each observation, while the allowed hydrogen lines transition from being narrow and single peaked with a broad base to broad and double peaked, with the blue peak suppressed relative to the red. This is a profile commonly seen in bipolar outflows (Steele et al 2011). The separation between peaks observed in the H α profile in 2015 is an order of magnitude higher than one would expect from a Keplerian disc at au scales.…”
Section: Spectroscopymentioning
confidence: 64%
“…As discussed in Section 3.4, the nebular emission lines are broad in each observation, while the allowed hydrogen lines transition from being narrow and single peaked with a broad base to broad and double peaked, with the blue peak suppressed relative to the red. This is a profile commonly seen in bipolar outflows (Steele et al 2011). The separation between peaks observed in the H α profile in 2015 is an order of magnitude higher than one would expect from a Keplerian disc at au scales.…”
Section: Spectroscopymentioning
confidence: 64%
“…For example, a radiatively-driven wind could occur at large (< ∼ 4.6 pc) radii given an initial impulse from the early > ∼ 10 43 erg s −1 flare. Such winds have been attributed to [O III] emission from the Virgo elliptical galaxy NGC4472 globular cluster RZ 2109, possibly in conjunction with a stellar-mass black hole, and require relatively little gas mass (< ∼ 10 −3 M⊙ for L λ5007 ∼ 10 37 erg s −1 Steele et al 2011). Such gas likely exceeds the escape velocity of the galaxy.…”
Section: Discussionmentioning
confidence: 99%
“…We have been monitoring the [OIII]λλ4959,5007 emission of RZ2109 since 2007 to examine how the emission has changed over time, and how changes in the optical emission compare to any changes in the X-ray luminosity. Figure 3 plots the full [OIII]λ5007 equivalent widths from Steele et al (2011) and Table 1 to the X-ray luminosities of RZ2109 taken from Maccarone et al (2010), Dage et al (2018), and Table 2.…”
Section: Time Evolution Of the [Oiii] Emissionmentioning
confidence: 99%
“…Optical spectroscopy obtained by Zepf et al (2007) revealed a very broad and luminous [OIII]λλ4959,5007 emission lines, with a velocity width of around 2000 km s −1 . The oxygen emission is also variable (Steele et al 2011). RZ2109 is the only globular cluster associated with NGC 4472 to show [OIII]5007 emission, which places constraints on geometric beaming of the system.…”
Section: Introductionmentioning
confidence: 99%